Organic Hydroperoxide Resistance Gene ohr (VPA1681) Confers Protection against Organic Peroxides in the Presence of Alkyl Hydroperoxide Reductase Genes in Vibrio parahaemolyticus - Chen, Ning-Xin; Chu, Ying-Jr; Ni, Bin; Hsu, Paula; Wong, Hin-chung (Applied and environmental microbiology, 2021)
Vibrio parahaemolyticus is the most prevalent foodborne pathogen in Taiwan and some other coastal Asian countries, and its antioxidative activity contributes to the tolerance of this bacterium to different environmental stresses. This study reports on the function of the organic hydroperoxide resistance gene ( ohr ; VPA1681) and its gene regulator ohrR (VPA1682) in this pathogen. The marine foodborne enteropathogen Vibrio parahaemolyticus contains the chief organic peroxide reductases AphC1-AhpC2 and a putative organic hydroperoxide resistance enzyme (Ohr; VPA1681) against different peroxides. This study investigated the function of the Ohr under the presence of AhpC1-AhpC2 in this pathogen by gene mutation. Experimental results demonstrated that the ohr gene product was a weak scavenger of H 2 O 2 only in the mutant strains that lacked the peroxide sensor/regulator oxyR and ahpC1 - ahpC2 genes. The Ohr of V. parahaemolyticus was highly effective at scavenging organic peroxide, as demonstrated by assaying the defective changes in the Δ ohr mutant strain and determining the detoxifying activity of the purified recombinant V. parahaemolyticus Ohr vp protein in the reduced form. The Ohr and AhpC1-AhpC2 exhibited similar functions against organic peroxides; however, only the ΔahpC1ΔahpC2 mutant strain showed a significant increase in susceptibility to several disinfectants, organic acids, and antibiotics compared with the wild-type strain. The transcription of the ohr gene depended on exogenous cumene hydroperoxide (cumene) stress and was markedly enhanced in the ΔohrR (VPA1682) mutant strains. This study revealed the organic hydroperoxide reductase activity of the Ohr in V. parahaemolyticus , and its role probably depends on sophisticated regulation by OhrR. IMPORTANCE Vibrio parahaemolyticus is the most prevalent foodborne pathogen in Taiwan and some other coastal Asian countries, and its antioxidative activity contributes to the tolerance of this bacterium to different environmental stresses. This study reports on the function of the organic hydroperoxide resistance gene ( ohr ; VPA1681) and its gene regulator, ohrR (VPA1682), in this pathogen. The strain with the ohr gene had effective protection against organic peroxide, and the recombinant Ohr vp was active in its reduced form. The function of Ohr was significant mostly in strains in which the function of AhpC1-AhpC2 was limited. The ohrR repressor of the ohr gene was effective at low concentrations of organic peroxide. Other common Vibrio species that contain homologous ohr , ohrR , ahpC1 , and ahpC2 genes, which are phylogenetically close to those of V. parahaemolyticus , may share similar functions to those revealed in this study.